Metafiction and Cyborg Detectives: identity technodilemmas in Lágrimas en la lluvia and Blade Runner - Morera, Mario (2022)
Spanish writer, Rosa Montero, created a sci-fi trilogy composed by Lágrimas en la lluvia (2011), El peso del corazón (2015) and Los tiempos del odio (2018). Her main character, the cyborg detective Bruna Husky, lives in the future 2109 Madrid amidst a series of adventures that resemble posthumanist metafictional connections with the movie Blade Runner (1982 and 2007 versions), by Ridley Scott. This article proposes a metafictional, comparative analysis of the first novel of her series and Scott’s film in order to create a posthumanist approach regarding identity issues in cyborg detectives and the potential reactions of noir detective literature and film.